2015
DOI: 10.1111/apel.12094
|View full text |Cite
|
Sign up to set email alerts
|

FDI productivity spillovers and the technology gap in Malaysia's electrical and electronic industries

Abstract: This study measures the impact of indirect technology transfer through spillovers from foreign direct investment (FDI) on Malaysia's development of a 'high-tech' sector, namely the electrical and electronic (E&E) industries. We estimate the total factor productivity (TFP) of establishments as a function of foreign presence within and across industries. Both the fixed assets and wages share of foreign establishments in a five-digit ISIC (International Standard Industrial Classification) industry are used as mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 53 publications
(114 reference statements)
1
17
1
Order By: Relevance
“…Also, in-house training centres of skill-oriented MNCs facilitated horizontal spillovers as many ex-MNC-trained local employees set up local establishments such as Unisem, Carsem, and Globtronics in the same industry (Best and Rasiah 2003). This is contrary to the findings of Khalifah et al (2015), while augmenting the spillover literature whereby accounting for workers' skills (instead of only wages or capital) may provide better evidence of productivity spillovers in the Malaysian manufacturing sector. Another important observation is the absence of spillovers through forward linkages in all the four characteristics of interest.…”
Section: Resultscontrasting
confidence: 93%
See 2 more Smart Citations
“…Also, in-house training centres of skill-oriented MNCs facilitated horizontal spillovers as many ex-MNC-trained local employees set up local establishments such as Unisem, Carsem, and Globtronics in the same industry (Best and Rasiah 2003). This is contrary to the findings of Khalifah et al (2015), while augmenting the spillover literature whereby accounting for workers' skills (instead of only wages or capital) may provide better evidence of productivity spillovers in the Malaysian manufacturing sector. Another important observation is the absence of spillovers through forward linkages in all the four characteristics of interest.…”
Section: Resultscontrasting
confidence: 93%
“…13 A caveat to this finding is that different industries may exhibit different outcomes. For example, Khalifah et al (2015) found negative spillovers in E&E industries, in part due to the lack of demand from foreign firms for locally supplied intermediate goods.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, modified and improved technology tools can reduce the cost of production (Olatunji & Ibidunni, 2013). To the best of our knowledge, only Khalifah et al (2015) and Khalifah and Jaafar (2017) who study TE of electrical and electronic manufacturing industry in Malaysia use data at the industry level. However, Khalifah et al (2015) discuss the effect of indirect technology transfer on foreign direct investment (FDI).…”
Section: Literature Reviewmentioning
confidence: 99%
“…There is also no consideration on the determinants of technical inefficiency such as Mahadevan (2002a;2002b;2002c) and Sulaiman (2012). In fact, recent studies such as by Khalifah et al (2015), and Khalifah and Jaafar (2017) used data at the industry level but not really use cross-sectional data at the firm or micro level. As a result, the level of TE obtained is not significant.…”
Section: Introductionmentioning
confidence: 99%